Selection of a Novel DNA Aptamer Specific for 5-Hydroxymethylfurfural Using Capture-SELEX - Xixia Liu; Yingyu Hou; Yanlin Qin; Jiaxin Cheng; Jianjun Hou; Qin Wu; Zhenmin Liu (Biosensors, 2023)
A capture systematic evolution of ligands by exponential enrichment (Capture-SELEX) was described to discover novel aptamers specific for 5-hydroxymethylfurfural (5-HMF), and a biosensor based on molecular beacon was constructed to detect 5-HMF. The ssDNA library was immobilized to streptavidin (SA) resin to select the specific aptamer. The selection progress was monitored using real-time quantitative PCR (Q-PCR), and the enriched library was sequenced by high-throughput sequencing (HTS). Candidate and mutant aptamers were selected and identified by Isothermal Titration Calorimetry (ITC). The FAM-aptamer and BHQ1-cDNA were designed as the quenching biosensor to detect 5-HMF in milk matrix. After the 18th round selection, the Ct value decreased from 9.09 to 8.79, indicating that the library was enriched. The HTS results indicated that the total sequence numbers for 9th, 13th, 16th, and 18th were 417054, 407987, 307666, and 259867, but the number of sequences for the top 300 sequences was gradually increased from 9th to 18th, and the ClustalX2 analysis showed that there were four families with high homology rate. ITC results indicated that the Kd values of H1 and its mutants H1-8, H1-12, H1-14, and H1-21 were 2.5 μM, 1.8 μM, 1.2 μM, 6.5 μM, and 4.7 μM. The linear range of the quenching biosensor was from 0 μM to 75 μM, and it had a similar linear range in the 0.1% milk matrix. This is the first report to select a novel aptamer specific for 5-HMF and develop quenching biosensor for the rapid detection of 5-HMF in milk matrix.